The Marcan Framework - Sawyerr, Harry (Scottish journal of theology, 1961)
In 1932, Professor Dodd published in the Expository Times an article on ‘The Order of Events in St. Mark's Gospel' which broke fresh ground in the Study of that Gospel. Dr Dodd then stated that in planning the first ten chapters St. Mark had a skeleton outline of our Lord's earthly career which he broke up into what now stand as editorial summaries. This outline he suggested was in the nature of a summary of the kerygma and approximated to the Petrine speech of Acts 10.37–41 or the Pauline speech in Acts 13.23–31. Into this outline were inserted the pericopae Mark collected sometimes on a historical, and at other times on a topical basis. This hypothesis held the field for a considerable time but it has recently been questioned by Professor Nineham in an examination of Dr Dodd's hypothesis in his contribution to Studies in the Gospels published in 1955. Indeed Professor Nineham takes the line that the presupposition of such a skeleton outline of our Lord's ministry which Mark used in the way Dr Dodd suggests is ‘highly improbable’.1 He questions the probability of such an outline having been preserved by the early Church. Referring to the changes in the Marcan pattern which both Matthew and Luke felt free to introduce when using St. Mark's Gospel as a basis, and to the difference in outlook between St. John's Gospel and the Synoptics, he concludes: ‘It does not appear that the precise order in which the saving events occurred seemed to the early Christian mind a very vital element in the saving proclamation or kerygma.'2 Professor Nineham is of course prepared to admit that the Passion narrative is in a class by itself and does not appear to question the accepted opinions of scholars that it was an early compilation of the primitive Church. But he rightly contends that there is no cogent evidence that the Church quite early agreed on ‘a formal outline account of the progress of the Lord's earthly ministry’.3